Safety Investigations of Two Formulations for Vaginal Use Obtained from Eugenia uniflora L. Leaves in Female Rats - Guilherme Donadel; Mariana Dalmagro; João Antonio Berta de Oliveira; Giuliana Zardeto; Mariana Moraes Pinc; Jaqueline Hoscheid; Odair Alberton; Salviano Tramontin Belettini; Ezilda Jacomassi; Arquimedes Gasparotto Junior; Emerson Luiz Botelho Lourenço (MDPI AG, 2022)
Medicinal plants have great prominence in research into the development of new medicines. Eugenia uniflora L. (Myrtaceae) is an edible and medicinal plant with economic value in the northeast region of Brazil. Several preparations from E. uniflora leaves and its fruits are employed as a source of nutrients and bioactive compounds. In this study we evaluated the preclinical toxicology of crude extract and vaginal gel obtained from the leaves of E. uniflora (5%, 10%, and 15%) aiming to provide safety for its use in the treatment of vulvovaginitis. Both formulations were applied to the vaginal cavity for 14 days. Detailed observations of the vaginal region, including pruritus, swelling, irritation, burning, pain, and vaginal secretion, as well as the estrous cycle were evaluated. On the fifth day, blood samples were obtained from the supraorbital plexus for biochemical and hematological analyses. The animals were subsequently euthanized. All animals underwent necropsy and macroscopic examination of the vaginal mucosa and reproductive system. A histological examination was also performed. No clinically significant changes were detected during the entire experimental period. All biochemical, hematological, or histopathological parameters were within the normal range for the species. The data obtained allow us to suggest that the E. uniflora vaginal formulations are safe in this experimental model.